2015
DOI: 10.1016/j.gr.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic imaging of the underthrusting Indian slab and mantle upwelling beneath central Tibet

Abstract: To better understand the pattern of convergence between the Indian and Eurasian plates, we determine a high-resolution P-wave tomography of the crust and upper mantle under southern to central Tibet using a large number of high-quality data collected by the ANTILOPE-II and Hi-CLIMB projects. A significant low-velocity zone is detected above the northward underthrusting Indian slab beneath the Indus-Tsangpo suture, which may reflect fault zones or (incomplete) fragmentation as well as melts and/or fluids associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 82 publications
6
16
1
Order By: Relevance
“…As the most effective and practical geophysical methods, seismic imaging (Gao et al 2013;Karplus et al 2011;Kind et al 2002;Nabelek et al 2009;Nabelek and Nabelek 2014;Xu et al 2015a, b;Zhang et al 2011Zhang et al , 2013Zhao et al 2011Zhao et al , 2014aZhao and Nelson 1993) and magnetotelluric (MT) data modeling (Chen et al 1996;Le Pape et al 2012;Unsworth et al 2004Unsworth et al , 2005Wei et al 2001) have been widely applied to study the deep evolution and tectonic processes of the plateau over the past decades. Results of previous seismological studies have revealed some details for the extension Liang et al 2016;Tian et al 2015;Xu et al 2015a;Zhang et al 2015Zhang et al , 2016Zhang et al , 2011Zhao et al 2014b) and we believe that MT data can provide some indirect information to obtain a more comprehensive model. In this paper, we reprocessed previous MT data that were deployed in southern Tibet (Fig.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…As the most effective and practical geophysical methods, seismic imaging (Gao et al 2013;Karplus et al 2011;Kind et al 2002;Nabelek et al 2009;Nabelek and Nabelek 2014;Xu et al 2015a, b;Zhang et al 2011Zhang et al , 2013Zhao et al 2011Zhao et al , 2014aZhao and Nelson 1993) and magnetotelluric (MT) data modeling (Chen et al 1996;Le Pape et al 2012;Unsworth et al 2004Unsworth et al , 2005Wei et al 2001) have been widely applied to study the deep evolution and tectonic processes of the plateau over the past decades. Results of previous seismological studies have revealed some details for the extension Liang et al 2016;Tian et al 2015;Xu et al 2015a;Zhang et al 2015Zhang et al , 2016Zhang et al , 2011Zhao et al 2014b) and we believe that MT data can provide some indirect information to obtain a more comprehensive model. In this paper, we reprocessed previous MT data that were deployed in southern Tibet (Fig.…”
Section: Introductionmentioning
confidence: 75%
“…Seismic studies in western Tibet indicate that low-velocity zones exist widely in the middle crust and high velocity anomalies are imaged in the lower crust beneath southern Tibet and the hypothesis of radiogenic heating source appears to be unreasonable . Zhang et al (2015) suggest a LVZ above the northward underthrusting Indian slab beneath the YZS due to melts and/or fluids associated with the dehydration of the Indian plate. Unsworth et al (2005) discuss the crustal rheology beneath the Himalaya and southern Tibet by establishing a relationship between MT data and the partial melt fraction to obtain the effective viscosity.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of substantial azimuthal anisotropy beneath Tibet is well established in studies using different techniques and data types, including surface-wave imaging (e.g., Griot et al 1998;Huang et al 2004;Su et al 2008;Yao et al 2010;Yi et al 2010;Yang et al 2010b;Ceylan et al 2012;Legendre et al 2015;Pandey et al 2015;Schaeffer et al 2016;Xie et al 2016;Chen et al 2016), shear-wave splitting analysis (e.g., McNamara et al 1994;Hirn et al 1995;Sandvol et al 1997;Sol et al 2007;Zhao et al 2010;Leon Soto et al 2012;Eken et al 2013;Chang et al 2015;Wu et al 2015a;Chen et al 2015;Liu et al 2016;Singh et al 2016;Ye et al 2016), receiver functions (e.g., Vergne et al 2003;Levin et al 2008;Shen et al 2015;Liu et al 2015;Kong et al 2016), attenuation studies (Bao et al 2012) and P-wave arrival times (e.g., Wei et al 2013;Huang et al 2014;Zhang et al 2016b;Wei et al 2016). Radial anisotropy (the difference between the vertically and horizontally polarized waves: V SV and V SH , respectively, in the case of S waves) is also well documented (e.g., Shapiro et al 2004;Huang et al 2010;Duret et al 2010;Guo et al 2012;Xie et al 2013;Li et al 2016).…”
Section: Azimuthal and Radial Anisotropy Beneath Tibet: A Brief Synthmentioning
confidence: 99%
“…The subducting Indian plate is clearly imaged as a high-V zone beneath western, central and eastern parts of Tibet by teleseismic tomography using data recorded by portable seismic stations so far deployed along several profiles in the Tibetan Plateau (e.g., Zhang et al , 2014Zhao et al 2014). A typical example is the Indian lithosphere that is descending beneath the Eurasian plate, resulting in the Tibetan Plateau.…”
Section: Continental Plate Subductionsmentioning
confidence: 99%